Determination of Indoor Air Quality in Archives and Biodeterioration of the Documentary Heritage - Borrego, Sofía (2012)
Fil: Borrego, Sofía. Laboratory of Preventive Conservation. National Archive of the Republic of Cuba. Havana; Cuba